1979
DOI: 10.1111/j.1365-2133.1979.tb15299.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous lupus erythematosus and autoimmune thyroiditis

Abstract: A 19-year-old girl presented with cutaneous lupus erythematosus and hypothyroidism, and developed a thyrotoxic crisis when chloroquine therapy was discontinued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Previous epidemiologic studies have shown that patients with LE have an increased risk of comorbidity . In our study, we found an increased risk of Sjögren syndrome, as well as endocrine and respiratory diseases in SLE patients, regardless the CLE subtypes.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Previous epidemiologic studies have shown that patients with LE have an increased risk of comorbidity . In our study, we found an increased risk of Sjögren syndrome, as well as endocrine and respiratory diseases in SLE patients, regardless the CLE subtypes.…”
Section: Resultssupporting
confidence: 67%
“…Previous epidemiologic studies have shown that patients with LE have an increased risk of comorbidity. [14][15][16][17][18][19][20][21] In our study, we found an increased risk of Sj€ ogren syndrome, as well as endocrine and respiratory diseases in SLE patients, regardless the CLE subtypes. An association among cardiovascular and gastrointestinal diseases and age was shown; accordingly, patients with vs. those without such diseases were older.…”
Section: Smoking Pregnancy and Estrogens Treatmentsmentioning
confidence: 71%
“…Other autoimmune associations observed in this study were systemic sclerosis, thyroid dysfunction (in the form of thyroiditis, hypothyroidism, hyperthyroidism and goiter) and vitiligo that have been reported in literature. 20 DLE with PLE, vitiligo and primary localized cutaneous amyloidosis in lupus erythematosus have been previously reported in literature. [21][22][23]…”
Section: Course Of Dle and Its Association With Slementioning
confidence: 89%
“…It is well known that the combination of autoimmune thyroiditis with other autoimmune diseases (9) such as SLE, RA, and pernicious anemia is common. Meer-Roosen et al (10) demonstrated a case of the cutaneous LE and autoimmune thyroiditis. Callen et al (11) reported a case of Hashimoto's thyroiditis (HT) and bullous pemphigoid (BP); and they suggested an association of autoimmune pathogenesis between HT and BP.…”
Section: Commentmentioning
confidence: 99%